METHODS OF USING ROLE-PLAYING GAMES IN THE FORMATION OF PROFESSIONAL COMPETENCIES OF BANKING PROFESSIONALS ON A PRACTICAL EXAMPLE - Shishkina, T. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
In the scientific article the essence and significance of learning through play or game learning are determined in the training of future bank employees on a practical example of a role-playing game. Increasing demands on the quality of professional training of future bank employees for the effective work in terms of development of market relations of the current economic instability, crisis phenomena in the financial and banking sphere, the process of professional training of future bankers requires the use of modern methods and teaching methods, especially those that form the active creative activity of students. Learning through play or game learning is such active teaching method with modern advances of computer technology, the global Internet network. The methods of active learning are a set of means of organization and management of training and learning activity. These methods are characterized by the following factors: forced students’ activity, independent decision making in conditions of increased motivation and emotionality, constant interaction of the educational system and students. The examples of teacher-student interaction were analyzed. In the scenario of role play the knowledge, skills and abilities are practically defined that student should learn after participating in the roleplaying game. The complete scenario of the role-play "Credit insurance" is provided, which consists of the preparation of game, goals, the game content, time-stamped scenario and results. The head of the game is the teacher who conducts practical classes. The game is conducted at the practical lesson on the discipline "Insurance Culture" after the lecture "Insurance Culture in Deposit Insurance and Financial and Credit Risks" Students’ activity is increasing during role and business games, which is an important factor in receiving of a significant amount of knowledge and building skills and competencies for the same period of time on the traditional method of teaching (seminars and practical classes).